2022
DOI: 10.1111/acel.13754
|View full text |Cite
|
Sign up to set email alerts
|

Oral nicotinamide riboside raises NAD+ and lowers biomarkers of neurodegenerative pathology in plasma extracellular vesicles enriched for neuronal origin

Abstract: Declining nicotinamide adenine dinucleotide (NAD+) concentration in the brain during aging contributes to metabolic and cellular dysfunction and is implicated in the pathogenesis of aging‐associated neurological disorders. Experimental therapies aimed at boosting brain NAD+ levels normalize several neurodegenerative phenotypes in animal models, motivating their clinical translation. Dietary intake of NAD+ precursors, such as nicotinamide riboside (NR), is a safe and effective avenue for augmenting NAD+ levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…After FDR correction (cut-off p<0.1), the main pathways affected included alanine, aspartate, and glutamate metabolism; purine biosynthesis; arginine biosynthesis; pyrimidine metabolism; and nicotinate and nicotinamide metabolism (Fig 2C , Table 1). The affected pathway of nicotinate and nicotinamide metabolism confirms the accuracy of pathway analysis employed, based on abundant literature showing that aging is associated with declines in NAD + reserves and biosynthesis (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). The nonoverlapping FA metabolites were added into the list containing overlapping metabolites and the new list was queried for pathway alterations.…”
Section: Aging Influence On Pfc Metabolitesmentioning
confidence: 59%
“…After FDR correction (cut-off p<0.1), the main pathways affected included alanine, aspartate, and glutamate metabolism; purine biosynthesis; arginine biosynthesis; pyrimidine metabolism; and nicotinate and nicotinamide metabolism (Fig 2C , Table 1). The affected pathway of nicotinate and nicotinamide metabolism confirms the accuracy of pathway analysis employed, based on abundant literature showing that aging is associated with declines in NAD + reserves and biosynthesis (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). The nonoverlapping FA metabolites were added into the list containing overlapping metabolites and the new list was queried for pathway alterations.…”
Section: Aging Influence On Pfc Metabolitesmentioning
confidence: 59%
“…Yet, to this date, experiments have not directly addressed these hypotheses. On the other hand, cumulative evidence supports the use of L1CAM as a target for the isolation of blood-borne nEVs, including the enrichment of EV and neuronal markers in L1CAM IP eluates from human blood as well as the correlation of EV cargo with brain disease states and therapeutic interventions [ 54 , 76 84 ], the recovery of GFP-positive EVs from the plasma of Nestin-GFP mice selectively expressing GFP in neurons [ 79 ], and the positive correlations between brain and nEV levels of pathological proteins in multiple AD mouse models [ 43 ]. In addition, proteomic analyses have detected L1CAM in EVs isolated from human brains [ 85 , 86 ] and that a high percentage of proteins carried by EVs isolated from human blood via L1CAM IP are highly expressed in the human brain and shared by EVs isolated from the conditioned media of human neurons in culture [ 83 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies showed that oral supplementation of NA 12 , NR [33][34][35] or NMN 17,36 can increase the blood NAD + level and lead to beneficial outcomes. However, the conventional quantification based on HPLC-MS or enzymatic cycling assays are time-and labor-intensive, hence limiting the up-scale and generalization of the NAD + blood test.…”
Section: Discussionmentioning
confidence: 99%